2021
DOI: 10.1080/17458080.2021.1959032
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanism on Ni-C2-NS single-atom catalysis for the efficient CO2reduction reaction

Abstract: Ni-based single-atom catalysis (Ni-SAC) has been experimentally reported with superior performance in reducing CO 2 to CO. However, due to the ambiguities in its structures, the active sites of Ni-SAC that are responsible for superior performance have not yet been resolved. This work investigates the CO 2 reduction reaction (CO 2 RR) mechanism on Ni-SAC by carrying out quantum mechanics (QM) simulation to consider both solvation effects. After exploring multiple possible combinations of N, S, and C, we disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The changes in the free energy steps are very small in the whole free energy profile. Therefore, we can infer that the effect of solvent is not sufficient to change the reaction mechanism, as has also been reported in previous studies [87][88][89] .…”
Section: Figure 3bsupporting
confidence: 69%
See 1 more Smart Citation
“…The changes in the free energy steps are very small in the whole free energy profile. Therefore, we can infer that the effect of solvent is not sufficient to change the reaction mechanism, as has also been reported in previous studies [87][88][89] .…”
Section: Figure 3bsupporting
confidence: 69%
“…Therefore, we can infer that the effect of solvent is not sufficient to change the reaction mechanism, as has also been reported in previous studies. [87][88][89]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the oxAGDY-full system carrying the most imino groups could also work as a photocatalyst for CO 2 reduction reactions (CO 2 RRs), e.g., the reaction CO 2 + 2H + + 2e – → CO + H 2 O, according to its reduction potential at pH = 7, as indicated in Figure , whereas the reaction at the anode is still the OER with H 2 O molecules. The variations of the Gibbs free energies during the CO 2 RR process at the cathode have also been estimated by following the definitions as reported in the previous work . The step graph containing the free energy information is exhibited in Figure c.…”
Section: Resultsmentioning
confidence: 99%
“…The variations of the Gibbs free energies during the CO 2 RR process at the cathode have also been estimated by following the definitions as reported in the previous work. 68 The step graph containing the free energy…”
Section: Electronic Configurationsmentioning
confidence: 99%
“…149 A similar study revealed that Ni-SACs with two C, one N, and one S coordination environment were estimated to be the most efficient catalyst for the CO 2 RR, with a theoretically calculated onset potential of 0.67 eV. 150…”
Section: Insights From Computational Studiesmentioning
confidence: 93%